The Effect of Live Streaming, Content Marketing, and Customer Trust on Purchase Decision Among Generation Z Users of Social Commerce on TikTok - Zatu Kiasati; Aida Sari (International Forum of Researchers and Lecturers, 2025)
The advancement of the digital era has provided a significant platform for shopping. In this context, factors such as live streaming, content marketing, and customer trust play a crucial role in influencing consumers’ purchasing decisions on TikTok social commerce. This study aims to examine the impact of live streaming, content marketing, and customer trust on the purchasing decisions of Generation Z users of TikTok’s social commerce at the Faculty of Economics and Business, University of Lampung. With the rapid growth of social media-based e- commerce, these factors have become critical in determining consumer purchasing decisions. Data was collected through a questionnaire designed using Google Forms and distributed to 115 respondents using a non-probability sampling method and purposive sampling technique. Data analysis was performed using SPSS version 26. The analytical methods used included multiple linear regression and hypothesis testing through t-tests and F-tests. The results of the study show that all three independent variables, namely live streaming, content marketing, and customer trust, have a positive and significant impact on purchasing decisions. These findings suggest that marketing strategies based on live streaming, engaging content, and efforts to build consumer trust can enhance purchasing decisions in social commerce.